THE EFFECT OF POVIDONE IODINE INTRARECTAL TO REDUCE BACTERIURIA, BACTEREMIA, AND SIRS AFTER TRUS PROSTATE BIOPSY - Aulia, Rifky; Rizaldi, Fikri; Hardjowijoto, Sunaryo (Indonesian Journal of Urology, 2018)
Objective: To compare the incidence of bacteruria, bacteremia, and Systemic Inflammatory Response Syndrome (SIRS) after Transrectal Ultrasound (TRUS) of prostate biopsy for the patients whom given intrarectal povidone iodine, enema, prophylactic antibiotic with given enema and prophylactic antibiotic. Material & Methods: A Randomised, experimental study, 20 samples of men with suspicious of prostate cancer were divided into two groups, first group (control) were given enema (dulcolax supp 10 mg) and prophylactic antibiotic (ciprofloxacin 1000 mg), second group (treatment) were given enema (dulcolax supp 10 mg) prophylactic antibiotic (ciprofloxacin 1000 mg), and intrarectal povidone iodine befotre TRUS of prostate biopsy. Urine and rectal swab culture examination were performed before biopsy then urine, blood culture, and blood leucocyte 2 days after biopsy. To assess any bacterial translocation from rectum to urinary tract, we match the post biopsy urine culture antibiogram and rectal swab culture antibiogram before biopsy. Complications and serious adverse effects were also monitored. Outcomes were assessed using Unpaired T Test and Mann Whitney depends on the data distribution and homogeneity. Results: There was no significant difference bacteriuria between groups (p=0.26). Bacteremia and SIRS were not found within two groups 2 days after prostate biopsy.  Post biopsy bacteriuria positive patients antibiogram were compared with pre biopsy swab rectal culture antibiogram, there was no significant difference between two groups. But, significant correlation of pre biopsy rectal swab culture with post biopsy urine culture (p=0.04) were noted. Conclusion: Intrarectal povidone iodine before TRUS of prostate biopsy were not needed as part of rectal preparation, since enema and prophylactic antibiotic was proven to decrease the incidence of bacteriuria, bacteremia, and SIRS after TRUS of prostate biopsy. The occurrance of bacteriuria were caused by bacterial translocation from rectum to urinary tract.